EFFECTS OF HUMIC ACID ADDITION TO FEEDS WITH HEAVY METAL CADMIUM CONTAMINATION FROM GREEN MUSSELS ON THE GROWTH PERFORMANCE OF ASIAN SEABASS - Rasidi Rasidi; Dedi Jusadi; Mia Setiawati; Munti Yuhana; Muhammad Zairin Jr.; Ketut Sugama (SEAMEO BIOTROP, 2019)
Although it contains heavy metals, the highly nutritious green mussel Perna viridis is used as a fish meal replacement in fish diets. Fortunately, humic acid (HA) has the ability to chelate heavy metals in animal feeds. Its addition to fish feed formulation is, therefore, needed to prevent the accumulation of heavy metals in the fish's body. Hence, an experiment using a Completely Randomized Design (CRD) with 5 treatments and 3 replications was conducted to evaluate the performance and feed efficiency of Asian seabass Lates calcarifer juveniles with the addition of HA to their green mussel–based diet containing the heavy metal cadmium (Cd). Five experimental diets were formulated with different dosages of HA addition at 0, 400, 800, 1200, and 1600 mg kg⁻¹ of feed as treatments A, B, C, D, and E, respectively. The experimental diets were given to triplicate groups of 15 Asian seabass juveniles with an initial body weight of 4.30 ± 0.60 g over a 70-day cultivation period, feeding until satiation. The results showed that feed consumption, feed digestibility, protein retention, growth performance, and feed efficiency were significantly affected by HA addition in the fish diet. Among all treatments, HA addition of 1600 mg kg⁻¹ produced the best biological response from the Asian seabass. To conclude, the HA addition of 1600 mg kg⁻¹ into the diet was the best dosage, resulting in optimal growth performance and feed efficiency in Asian seabass. The highest dose of HA in Cd-contaminated feeds could reduce Cd content, but had not yet been able to eliminate Cd in fish meat. Therefore, green mussel meal, with HA addition as an alternative protein source, has potential as a feed additive for Cd-contaminated diets of Asian seabass juveniles.